Potensi Lahan Pekarangan dan Pengetahuan Warga Kelurahan Bubulak Terhadap Pola Pertanaman dan Jenis Tanaman - Rifda Sajida; I Wayan Astika (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Utilization of the yard as agricultural land is one alternative to meet family food needs. Homeyards can be used as living barns, food stalls, or even living pharmacies. In general, there are twoobjectives of this activity, namely to be able to know the potential use of house yards as a cropcultivation area in Bubulak Village and to analyze the level of knowledge of Bubulak Villageresidents on plant cultivation techniques by utilizing home yards. Residents’ knowledge aboutcultivation techniques in the yard was measured through interviews. The data used are secondarydata and primary data. Sampling method used in sampel selection is the accidental sampling method,while the analytical method used is the descriptive analysis method. The results of this activityindicate that the residents' houses in Bubulak Village have the potential to be used as land forcultivation. In addition, The residents have have sufficient knowledge of horizontal croppingpatterns and potting media as well as about TOGA plant. However, knowledge of verticulture andvegetable cultivation is still very low. Counseling or socialization is needed for residents of Bubulak RW 6 related to cultivation techniques in the use of the yard, especially related to verticulturetechniques for vegetable crops.